The Effect of Vitamin C on Pathological Parameters and Survival Duration of Critically Ill Coronavirus Disease 2019 Patients: A Randomized Clinical Trial - Majidi, Nazanin; Rabbani, Faezeh; Gholami, Somayeh; Gholamalizadeh, Maryam; BourBour, Fatemeh; Rastgoo, Samira; Hajipour, Azadeh; Shadnoosh, Mahdi; Akbari, Mohammad Esmail; Bahar, Bojlul; Ashoori, Narjes; Alizadeh, Atiyeh; et al. (Frontiers in Immunology, 2021)
Introduction Vitamin C has been reported to have beneficial effects on patients with coronavirus disease 2019 (COVID-19). This study aimed to investigate the effect of vitamin C supplementation on pathological parameters and survival duration of critically ill patients with COVID-19. Methods This clinical trial was conducted on 120 hospitalized critically ill patients infected with COVID-19. The intervention group (n = 31) received one capsule of 500 mg of vitamin C daily for 14 days. The control group (n = 69) received the same nutrition except for vitamin C supplements. Measurement of pathological and biochemical parameters was performed at baseline and after 2 weeks of the intervention. Results Following 2 weeks of vitamin C supplementation, the level of serum K was significantly lower in the patients compared with the control group (3.93 vs. 4.21 mEq/L, p < 0.01). Vitamin C supplementation resulted in a higher mean survival duration compared with that of the control group (8 vs. 4 days, p < 0.01). There was a linear association between the number of days of vitamin C intake and survival duration (B = 1.66, p < 0.001). The vitamin C supplementation had no effect on blood glucose, mean arterial pressure, arterial blood gas (ABG) parameters, Glasgow Coma Scale (GCS), kidney function, cell blood count (CBC), hemoglobin (Hb), platelet (Plt), partial thromboplastin time (PTT), albumin, hematocrit (Hct), and other serum electrolytes including sodium (Na), calcium, and phosphorus (P). Conclusion The present study demonstrated the potential of vitamin C supplementation in enhancing the survival duration of critically ill patients with COVID-19. Clinical Trial Registration https://www.irct.ir/trial/55074, identifier IRCT20151226025699N5